2016
DOI: 10.1093/eurheartj/ehw526
|View full text |Cite
|
Sign up to set email alerts
|

Contractility sensor-guided optimization of cardiac resynchronization therapy: results from the RESPOND-CRT trial

Abstract: AimsAlthough cardiac resynchronization therapy (CRT) is effective in patients with systolic heart failure (HF) and a wide QRS interval, a substantial proportion of patients remain non-responsive. The SonR contractility sensor embedded in the right atrial lead enables individualized automatic optimization of the atrioventricular (AV) and interventricular (VV) timings. The RESPOND-CRT study investigated the safety and efficacy of the contractility sensor system in HF patients undergoing CRT.Methods and resultsRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 32 publications
3
93
0
2
Order By: Relevance
“…While single‐center studies have demonstrated the benefits of device optimization, the SmartAV randomized clinical trial using static algorithms failed to show a benefit of device‐based algorithms over echocardiographic optimization 24 . However, the Respond CRT randomized study of ambulatory optimization using an accelerometer sensor showed an improvement in clinical response compared with empirical programming, which was consistent across patient subgroups 25,26 . A dynamic algorithm such as aCRT will potentially maintain the benefits of optimal resynchronization during postural changes and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…While single‐center studies have demonstrated the benefits of device optimization, the SmartAV randomized clinical trial using static algorithms failed to show a benefit of device‐based algorithms over echocardiographic optimization 24 . However, the Respond CRT randomized study of ambulatory optimization using an accelerometer sensor showed an improvement in clinical response compared with empirical programming, which was consistent across patient subgroups 25,26 . A dynamic algorithm such as aCRT will potentially maintain the benefits of optimal resynchronization during postural changes and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, CRT has shown great potential in improving HF patients' survival, quality of life, symptoms, and exercise capacity, while reducing the need for hospitalizations . Nonetheless, despite significant improvements over the last decade and the introduction of many optimization strategies, 25% to 30% of patient are consistently considered clinical non‐responders across several studies . Multipoint LV pacing (MPP) is a novel LV pacing modality that might increase the magnitude of clinical, hemodynamic, and echocardiographic response to CRT, but uncertainty remains related to increased battery drain due to continuous pacing with an additional LV vector.…”
Section: Introductionmentioning
confidence: 99%
“…This allows continuous adaptation of the AV and VV interval setting of the CRT device according to the instantaneous needs of the patient [89]. A comparative study demonstrated that automatic optimization with the SonR sensor is as effective as echo-guided optimization, allowing the primary efficacy end point to be met with a 35% significant reduction in HF hospitalization rates during long-term follow-up [90]. …”
Section: Emerging Optimization Strategymentioning
confidence: 99%